2020
DOI: 10.1515/cclm-2020-0662
|View full text |Cite
|
Sign up to set email alerts
|

Association between SOX17, Wif-1 and RASSF1A promoter methylation status and response to chemotherapy in patients with metastatic gastric cancer

Abstract: To the Editor, Gastric cancer is one of the most frequently diagnosed cancers worldwide [1]. In 2020, it is estimated that there will be more than 27,000 new cases and more than 11,000 patients will die from the disease, in the United States [2]. A global epigenetic marker is methylation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In recent years, multiple studies have suggested a key role of abnormal methylation of certain genes in the occurrence and development of GC. DNA methylation analysis could provide information for early screening, efficacy, and prognostic assessment of patients with GC ( 16 , 17 ) and other types of cancer ( 18 ). Patients with widespread gene hypermethylation show a lower overall survival rate, suggesting a correlation between gene methylation and chemotherapy sensitivity ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiple studies have suggested a key role of abnormal methylation of certain genes in the occurrence and development of GC. DNA methylation analysis could provide information for early screening, efficacy, and prognostic assessment of patients with GC ( 16 , 17 ) and other types of cancer ( 18 ). Patients with widespread gene hypermethylation show a lower overall survival rate, suggesting a correlation between gene methylation and chemotherapy sensitivity ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of the promoter region of PD-L1 gene causes an overexpression of PD-L1 in prostate cancer and glioblastoma patients, leading to a more aggressive disease prognosis [6,7] . In addition, the methylation of the promoter region of several genes (e.g., SOX-17, Wif-1, RASSF1A) can lead to a decrease in progression-free survival (PFS) and overall survival (OS), as well as a decrease in the response to chemotherapy in patients with metastatic gastric adenocarcinoma [8,9] .…”
mentioning
confidence: 99%